Kinetic and rheological investigation of cyclopentane hydrate formation in waxy water-in-oil emulsions. (1st March 2021) - Chen, Yuchuan; Shi, Bohui; Fu, Shunkang; Li, Qingping; Yao, Haiyuan; Liu, Yang; Lv, Xiaofang; Wang, Junao; Liao, Qingyun; Duan, Xu; Gong, Jing
Abstract: Hydrates and waxes are supposed to coexist in the deep-water pipelines under suitable conditions of low temperature and high pressure. Understanding the effect of precipitated wax crystals on hydrate formation and rheological properties of hydrate slurry is crucial to the flow assurance in offshore petroleum production. In this work, a stress-controlled rheometer was used to carry out the rheological experiments for investigating the impact of wax crystals on hydrate formation and yield property of hydrate slurry. The effects of wax content and water cut on cyclopentane (CP) hydrate nucleation and growth were investigated in terms of the measured viscosity data. Log-normal distribution could well fit the probability density histogram of CP hydrate critical time. The logarithmic mean values of CP hydrate critical time decreased with increasing water cut but increased with increasing wax content in water-in-oil (w/o) emulsions. Semi-empirical models were proposed to describe the inhibitory effect of wax crystals on CP hydrate nucleation kinetics by considering the inhibition of mass transfer based on the Freundlich and Langmuir adsorption functions, respectively. Hydrate slurry viscosity rate showed the two-stage characteristics in wax-free w/o emulsions, while four stages could be clearly observed in waxy w/o emulsions. The maximum values of hydrate slurry viscosity rate and calculated hydrate effective volume fraction decreased with increasing wax content. Hydrate growth time was gradually extended as wax content increased. Furthermore, the measured yield stress and yield strain increased with increasing wax content at different water cuts, which was associated with the multiple effect of capillary bridge between hydrate particles, spatial network of wax crystals and coalescence of water droplets. At last, compared to the stress ramp rate, the influence of annealing time on yield stress was more significant.